Pengaruh Pendapatan Asli Daerah dan Belanja Modal Pada Kinerja Keuangan Pemerintah Daerah - Nilam Kencana Ningrat, Cok Istri; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p15, 2019)
This study aims to determine the effect of Regional Original Income and Capital Expenditures on Local Government Financial Performance. This research was conducted in 38 Regional Organizations (OPD) found in Gianyar Regency. This study uses secondary data, namely the report on the realization of the APBD in 2015-2017. Sampling uses a saturated sample technique. OPD selected as a sample of 36 OPDs. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of data analysis shows that the Regional Original Income variable has a positive and significant effect on the financial performance of local governments, while the capital expenditure variable has a negative and significant effect on the financial performance of local governments. Keywords : Regional Original Income;  Capital Expenditure;  Financial Performance.